L'Ombre - Amimer, Jerome (France, 2011)
This film documents the everyday sounds of the French town Oradour–Sur-Glane. Director Jerome Amimer searches for parallels between the sounds he records at Oradour-Sur-Glane and those which his late grandmother may have heard in her homeland of Russia.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films